What drives internal audit effectiveness? A systematic literature review of 20 years of evidence - Ramadhan, Rico Putra (Institute of Computer Science (IOCS), 2025)
Internal audit (IA) effectiveness is crucial in supporting good organizational governance. However, there are varied findings in the literature regarding the factors that influence IA effectiveness. This Systematic Literature Review (SLR) study aims to explore the factors driving internal audit (IA) effectiveness based on 20 years of evidence. Using data from 30 previous studies published from 2005-2025, the results are divided into three main findings. First QR 1, management support has been the most dominant factor for two decades, followed by IA independence and audit competence as the next dominant factors. Second QR 2, information technology (IT) emerged as the most prominent factor in studies between 2020-2025, explaining the shift toward new factors driving internal audit effectiveness. However, traditional factors such as management support remain relevant for now. Third QR 3, the findings emphasize the importance of synergy between management support and technology adoption to support internal audit, in addition to the need for regulators to develop future regulations that are adaptive to technological developments in internal audit practices